The discursive construction of identities on- and offline: personal - group - collective - Bös, Birte; Kleinke, Sonja; Mollin, Sandra; Hernández, Nuria (Discourse approaches to politics, society and culture, 2018)
Intro -- The Discursive Construction of Identities On- and Offline -- Editorial page -- Title page -- LCC data -- Table of contents -- Preface -- Introduction: Identity construction in complex discourse contexts -- 1. Introduction -- 2. Recasting sites of identity construction in the digital age -- 3. The lens of clusivity -- 4. Three strands of identity -- 5. The contributions -- References -- Part I. Personal identities -- Great pretenders: The phenomenon of impersonating (pseudo-)historical personae in medieval blogs, or: Blogging for someone else's fame? -- 1. Framing the objective -- 2. Browsing through relevant notions and frameworks -- 3. Blog, what art thou? - Assessing the surface levels of Chaucer's Blog -- 4. Framing the 'pretenders': Medieval aficionados, role-playing metagamers and fun "hunch-backed keepers of a dark culture and age"? -- 5. A brief conclusion regarding intentional frame breaks, or: Blogging for one's own fame after all (?) -- References -- Constructing personal identities online: Self-disclosure in popular blogs -- 1. Introduction -- 2. Theoretical background and research aims -- 3. Material -- 4. Analysis -- 5. Conclusions -- References -- The development of identity in Batman comics -- 1. Introduction -- 2. Data and methodology -- 3. Fictional dialogues and worlds -- 4. Reading for character and identity construction in comics -- 5. Characters in the DC Batman universe -- 6. Conversation analysis and the comics data -- 7. From Spoiler to Robin to Batgirl -- 8. Conclusion -- References -- Part II. Group identities -- Code-switching and identity construction in WhatsApp: Evidence from a (digital) community of practice -- 1. Introduction -- 2. Code-switching and group identity: Theoretical dimensions -- 3. WhatsApp as a socio-technical mode -- 4. Analysis of the WhatsApp data -- 5. Questionnaire results and discussion
Literaturangaben
Keywords: Electronic books; Konferenzschrift -- 2013 -- Heidelberg; Konferenzschrift -- 2015 -- Duisburg; Aufsatzsammlung; Computerunterstützte Kommunikation; Diskursanalyse; Identität